Cytokine BAFF released by Helicobacter pylori-infected macrophages triggers the Th17 response in human chronic gastritis - Munari, Fabio; Fassan, Matteo; Capitani, Nagaja; Codolo, Gaia; Vila-Caballer, Marian; Pizzi, Marco; Rugge, Massimo; Della Bella, Chiara; Troilo, Arianna; D'Elios, Sofia; Baldari, Cosima T; D'Elios, Mario M; et al. (The Journal of immunology (1950), 2014)
BAFF is a crucial cytokine that affects the activity of both innate and adaptive immune cells. It promotes the expansion of Th17 cells in autoimmune disorders. With this study, we investigated the BAFF/Th17 responses in Helicobacter pylori-induced gastritis in humans. Our results show that the mucosa from Helicobacter(+) patients with chronic gastritis is enriched in IL-17 and BAFF, whereas the two cytokines are weakly expressed in Helicobacter(-) patients with chronic gastritis; moreover, the expression of both BAFF and IL-17 decreases after bacteria eradication. We demonstrate that BAFF accumulates in macrophages in vivo and that it is produced by monocyte-derived macrophages in vitro, after Helicobacter stimulation. Application of BAFF on monocytes triggers the accumulation of reactive oxygen species that are crucial for the release of pro-Th17 cytokines, such as IL-23, IL-1β, and TGF-β. Moreover, BAFF directly promotes the differentiation of Th17 cells. In conclusion, our results support the notion that an axis BAFF/Th17 exists in chronic gastritis of Helicobacter(+) patients and that its presence strictly depends on the bacterium. Moreover, we demonstrated that BAFF is able to drive Th17 responses both indirectly, by creating a pro-Th17 cytokine milieu through the involvement of innate immune cells, and directly, via the differentiation of T cells toward the specific profile. The results obtained in this study are of great interest for Helicobacter-related diseases and the development of novel therapeutic strategies based on the inhibition of the BAFF/IL-17 response.